Community-Based Participatory Research in the News: A Qualitative Case Study of the Online Media Characterization of a French Health Study. Issue 2 (April 2020) - Duarte, Catherine dP.; Cohen, Alison K.; Allen, Barbara L.
Since online media can be key in the widespread, symmetrical dissemination of science, we performed a media content analysis of 44 online articles to assess coverage of a French community-based participatory research (CBPR) epidemiologic study. Most articles highlighted methodological rigor and the research topic's salience to residents. Approximately half of the articles reported findings, with the remaining focusing on action steps. To our knowledge, this study is the first to explore how online media communicate CBPR, a novel approach in the French context, to the public. Though there were some gaps in the media's portrayal, CBPR may facilitate online media uptake of findings. We provide recommendations for future research on this topic.